MODERN DESIGN TOOLS FROM THE PERSPECTIVE OF GRAPHIC DESIGN DEVELOPMENT - Almnshdawy Hussain Abdualee (Izdevnieciba "Baltija Publishing", 2023)
A scheme for considering design as a complex system with appropriate linguistics and a significant replenishment of the design system with new categories useful for further theoretical research and practical use is developed. The state of modern design is considered, its purpose is the expediency of existence, the harmony of the architectural and subject environment, the technical perfection of products with technological feasibility and economic efficiency, ergonomic comfort and environmental priority. Its social significance is the creation of a secure and decent way of life and work, artistic imagery of the object world, social self-organization and humanization of society, the formation of social consciousness, inspiration, purification, ennoblement of a person, his or her spiritual revival and recovery, the acquisition of labor and creative motivation and, as a result, the progressive economic development of society. The article discusses media design as an innovative development of design, paying attention to media design in the system of modern Internet technologies. Information and communication technologies as a set of methods and software and hardware expand the scope of media design in the information space, which contributes to the meaningful assimilation of information. Thanks to high-quality media design and its mobility, modern information Internet technologies provide relevance, selectivity, interactivity, multimedia, rapid production and distribution of interactive technologies.